Does Level of Blood Alcohol Content Affect Clinical Outcomes After Trauma in Older Adult Patients?. Issue 9 (September 2020) - Bryant, Mary K.; Reynolds, Katherine; Brittain, Connor; Patel, Zachery; Reid, Trista D.S.; Maine, Rebecca G.; Udekwu, Pascal
Introduction: Preinjury alcohol use and older age have independently been associated with poor outcomes. This study examined whether higher levels of blood alcohol concentration (BAC) correlated with an increased likelihood of poor outcomes in older trauma patients. Methods: This was a retrospective cohort study of injured patients ≥65 years with BAC testing presenting to a Level 1 trauma center between 2015 and 2018. Patients were stratified by BAC at 4 thresholds of intoxication: BAC ≧10 mg/dL, BAC ≧80 mg/dL, BAC ≧150 mg/dL, and BAC ≧200 mg/dL. Propensity score matching using inverse probability of treatment weighting was used to estimate outcomes. Logistic and Poisson regression models were performed for each threshold of the BAC level with the matched cohort to assess clinical outcomes. Results: Of all older patients (n = 3112), 32.5% (n = 1012) had BAC testing. In the matched cohort of 883 patients (76.7 ± 8.2 years; 48.1% female), 111 (12.5%) had BAC ≧10 mg/dL, 83 (74.8%) had BAC ≧80 mg/dL, 60 (54.1%) had BAC ≧150 mg/dL, and 37 (33.3%) had BAC ≧200 mg/dL. Falls (60.5%) and motor vehicle crashes (28.9%) were the most common mechanisms of injury. Median (IQR) of Injury Severity Score (ISS) was 5 (1-10). The risk of severe injury (ISS ≧15) was similar between alcohol-positive and alcohol-negative patients (9.9% vs 15.0%, P = .151). BAC ≧10 g/dL was not associated with length of stay, intensive care unit admission, or in-hospital complication, nor was any of the other 3 analyzed BAC thresholds. Conclusion: Overall, any detectable BAC along and increasing thresholds of BAC was not associated with poor in-hospital outcomes of older patients after trauma. Alcohol screening was low in this population, and intoxication may bias injury assessment, leading to mistriage of older trauma patients.